English language teachers' insights into continuous professional development: A cross-case exploration - Serhat Başar; Halenur Çeliktürk; İrem Çomoğlu (Literacy Trek, 2020)
This qualitative cross-case study explores and reflects on the insights of six English language teachers working at one secondary school and one tertiary level institution in Turkey regarding the Continuous Professional Development (CPD) practices offered by their institutions respectively. It also investigates what contextual factors interact with these teachers' insights and experiences about CPD as part of teacher education regarding within-case and cross-case differences. The data were collected through semi-structured interviews, written reflections and program documents and analysed using a descriptive coding strategy. The findings reveal that the participant teachers consider CPD as a customized, practice-focused, collaborative and reflective endeavour. Implications for future continuous professional development programs are also discussed.